2003
DOI: 10.1073/pnas.1432900100
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary genomics of inversions in Drosophila pseudoobscura : Evidence for epistasis

Abstract: Drosophila pseudoobscura harbors a rich polymorphism for paracentric inversions on the third chromosome, and the clines in the inversion frequencies across the southwestern United States indicate that strong natural selection operates on them. Isogenic inversion strains were made from isofemale lines collected from four localities, and eight molecular markers were mapped on the third chromosome. Nucleotide diversity was measured for these loci and formed the basis of an evolutionary genomic analysis. The loci … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
182
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(204 citation statements)
references
References 56 publications
19
182
2
Order By: Relevance
“…The low gene transfer between inversions (gene flux) for genes located inside the inverted region observed in some Drosophila species is in agreement with both hypotheses (Laayouni et al, 2003;Schaeffer et al, 2003;Munté et al, 2005;Hoffmann and Rieseberg, 2008). However, despite the fact that Dobzhansky (1950) detected a lower fitness of heterozygous individuals from different populations of D. pseudoobscura in laboratory experiments, molecular studies failed to detect genetic differentiation within inversions sampled from different populations (Schaeffer et al, 2003).…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…The low gene transfer between inversions (gene flux) for genes located inside the inverted region observed in some Drosophila species is in agreement with both hypotheses (Laayouni et al, 2003;Schaeffer et al, 2003;Munté et al, 2005;Hoffmann and Rieseberg, 2008). However, despite the fact that Dobzhansky (1950) detected a lower fitness of heterozygous individuals from different populations of D. pseudoobscura in laboratory experiments, molecular studies failed to detect genetic differentiation within inversions sampled from different populations (Schaeffer et al, 2003).…”
Section: Introductionsupporting
confidence: 74%
“…Low levels of gene flow can be ruled out, as in the present work no significant DNA sequence differentiation was detected comparing the same arrangement between populations independently of the gene location. Similarly, in D. pseudoobscura (Schaeffer et al, 2003), no genetic differentiation was found between populations within arrangements using genes located in the inverted region. In D. subobscura, no significant DNA sequence differentiation was found among three European populations (one from Holland and two from Spain) when analyzing restriction length polymorphism in O ST and O 3+4 arrangements (Rozas et al, 1995).…”
Section: Divergence Time Of Inversionsmentioning
confidence: 93%
See 1 more Smart Citation
“…More recent work on D. suboobscura has indicated that the frequencies of certain inversions within both natural and laboratory populations are strongly correlated with different temperature regimes and seasons (Orengo and Prevosti, 1996;Kamping and Van Delden, 1999). Clines in inversion frequency related to variation in life history, morphological, and fitness-related traits and correlated to different climatic conditions have been characterized in D. suboobscura (Prevosti et al, 1988;Orengo and Prevosti, 1996;Schaeffer et al, 2003), other fruit fly species (Inoue et al, 1984;Rodriguez et al, 2000), and in mosquitoes (Coluzzi et al, 1979). Interestingly, Rodriguez et al (2000) found that only inversions associated with positive effects on trait values or fitness were involved in a latitudinal cline of D. buzzatti; inversions that were associated with neutral and negative effects on trait values or fitness did not show latitudinal patterns.…”
Section: Conversion With Physical Limits On Recombination Chromosomalmentioning
confidence: 99%
“…The authors interpreted this result to mean that longer inversions may have a greater chance of becoming common because the longer the inversion, the greater the chance that it includes interacting genes. Most recently, Schaeffer et al (2003) found that strong selection appeared to have acted on inversions in D. suboobscura, and argued that the inversions may have evolved as an adaptation to suppress recombination within coadapted gene complexes strongly linked to fitness.…”
Section: Conversion With Physical Limits On Recombination Chromosomalmentioning
confidence: 99%